0819 Impact of Changing Middle and High School Start Times on Sleep, Extracurricular Activities, Homework, and Academic Engagement. (12th April 2019) - Meltzer, Lisa J; McNally, Janise; Wahlstrom, Kyla L; Plog, Amy E
Abstract: Introduction: Although it is recommended that middle and high schools start at/after 8:30 a.m., most districts in the United States have not delayed start times. In Fall 2017, the Cherry Creek School District delayed school start times (Middle School [MS]: 8:00 to 8:50 a.m.; High School [HS]: 7:10 to 8:20 a.m.). This study examined changes to student sleep, extracurricular activities, homework, and academic engagement. Methods: Students in grades 6-11 completed online surveys during school hours in Spring 2017 (pre-change n=15, 700) and Spring 2018 (post-change n=18, 607). Questions included weekday and weekend bedtime [BT], wake time [WT], and total sleep time [TST], extracurricular activity participation, sleepiness during homework, and academic engagement. Parents (n=5, 441) provided consent for a sample of students whose surveys were allowed to be linked year-to-year, as well as with demographic information. Results: On weekdays, MS students reported slightly later BT (8m), later WT (39m), and longer TST (31m); HS students reported slightly later BT (13m), significantly later WT (61m), and longer TST (48m). When controlling for free/reduced lunch (FRL) status and race, results were similar for HS students; however, sleep duration increased more for MS students who received FRL (19m vs. 10m, p =0.05). Post-change, weekend oversleep was reduced by 38m for MS and 59m for HS students, and significantly more students obtained sufficient sleep (MS [≥ 9h]: 38% vs. 44%; HS [≥ 8h]: 27% vs 58%). Overall MS participation in sports decreased by 8%, while participation in HS sports, MS/HS activities, or HS employment decreased by < 3%. Fewer students reported feeling too sleepy to do their homework for both MS (46% vs. 35%) and HS (71% vs. 56%). Scores on a measure of academic engagement were significantly higher after the start time change for both MS and HS students ( p <0.001). Conclusion: This large study with linked data demonstrates that MS and HS students benefit from later start times with increased sleep duration, less sleepiness while doing homework, minimal changes to extracurricular participation, and improved academic engagement. Support (If Any): Robert Wood Johnson Foundation